Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Siswa Kelas IV Pembelajaran IPA Tema 1 Subtema 1 SDN 122398 Pematang Siantar - Irfan Siagian; Lisbet Novianti Sihombing; Canni Loren Sianturi (JOURNAL SAINS STUDENT RESEARCH, 2023)
This research aims to determine: The influence of the Problem Based Learning Model on the Learning Outcomes of Class IV Students in Science Learning Theme 1 Subtheme 1 at SDN 122398 Pematang Siantar. The type of research used in this research is Quantitative Research, which states that quantitative research is research in the form of numbers and analysis using statistics. The research design that will be used is an experiment, in the form of Pre-Experimental Design which uses a "one group pretest posttest design" design. The sample in this study was the fourth grade students of SD Negeri 122398 Pematang Siantar, totaling 23 students, of which there were 8 boys and 15 girls. The instrument used in this research was multiple choice questions. The results of testing the research hypothesis are that there is a significant influence in this research from the data that has been tested. The data can be seen from the data analysis that the average results of the experimental class were obtained in the pretest (55.13) and posttest (80.87). Research results at the 0.05 level. Based on data analysis of pretest and posttest values, it shows that the sig (2-tailed) value is 0.00 < 0.05, where H_0 is rejected and H_is accepted. So it can be concluded that there is a significant influence on improving the learning outcomes of students who use the problem based learning model on the learning outcomes of class IV students in science learning theme 1 subtheme 1 at SDN 122398 Pematang Siantar Q.A 2022/2023.